Contribution of major SSTA modes to the climate variability of tropical cyclone genesis frequency over the western North Pacific. (3rd February 2016) - Yu, Jinhua; Chen, Cheng; Li, Tim; Zhao, Xiaotong; Xue, Huaxing; Sun, Qiying
Abstract: The Generalized Equilibrium Feedback Analysis method was used to isolate the contributions of major sea‐surface temperature anomaly (SSTA) modes over three oceanic basins to the climate variability of tropical cyclone (TC) genesis number (TCGN) in the peak TC season over the western North Pacific (WNP) between 1970 and 2012. The results show that TCGN variation has a statistically significant response to the first SST mode over the tropical North Pacific (TNP1), Indian Ocean (IOBM) and North Atlantic (NA1). The dominant SSTA modes in the three basins contribute 16.6, 12.1 and 13.6% of total TCGN variance, respectively. Among them, TNP1 and NA1 are primarily responsible for TCGN interdecadal variability, with a contribution of 22 and 14.5% to its interdecadal variance at 96 and 93% confidence levels, respectively. TCGN interannual variability, on the other hand, is significantly influenced by IOBM and NA1 with a contribution of 17.6 and 14.3% of the total interannual variance, respectively. The maximum TCGN variability centres are located in the central WNP and South China Sea. The former is primarily associated with responses of low‐level relative vorticity to TNP1 and NA1 and the latter is closely linked to the forcing from IOBM and NA1.